Evolution of graphene, graphene oxide, reduced graphene oxide: An exploratory study using citation network analysis - Sheji, Aman Sooraj; Sivan, Dawn; Jose, Rajan (Penerbit Universiti Malaysia Pahang, 2024)
Graphene and its synthesis, along with its derivatives, have been at the forefront of materials’ research since its discovery in 2004. An analysis done during Dec 2023 using the keywords “graphene” and “synthesis” revealed nearly 40,000 research papers including journal articles, conference proceedings, reviews, books and book chapters; analysis of this vast data is beyond human abilities and requires computational intelligence. One of the research methodologies employed in analysing such vast data is Citation Network Analysis (CNA). Choosing the threshold citation to be two, the CNA constituted a cluster containing 294,680 papers. Using CNA, this study categorises this extensive literature into 12 clusters, unveiling their main paths of evolution. Notably, the most active research area focuses on the development of electrode materials for electrochemical applications. Additional focal points include advanced photocatalysts, electrocatalytic nitrogen fixation, wideband electromagnetic wave absorption materials, catalysts for formic acid oxidation, and flame retardancy in epoxy resin. The preference for the modified Hummers' method for synthesising graphene oxide emerges prominently due to its scalability. The implications of these findings are profound, paving the way for advancements in graphene synthesis with widespread impacts in industrial applications. By examining the historical trajectory of graphene research, this study offers critical insights, guiding future research endeavours in advanced materials science